2012
DOI: 10.11004/kosacs.2012.3.4.010
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Blast Resistant CFRP-steel Composite Structure Based on Reliability Analysis

Abstract: This study presents the effectiveness of a composite structure at improving blast resistance. The proposed composite structure consists of carbon fiber reinforced polymer (CFRP) and steel layers. While CFRP layer is used for blast energy reflection due to its high strength, steel layer is used for blast energy absorption due to its high ductility. A dynamic model is used to simulate the elastoplastic behavior of the proposed composite structure subject to blast load. Considering the magnitude variations of a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…The titanium layer and the aluminum layer were simulated as reflecting and absorbing members, respectively. Moreover, the optimal hybrid system containing CFRP and steel layers that was subjected to the same explosion source was also found with the present work [ 23 ]; the CFRP layer was considered as a reflecting layer, and the steel layer was considered as an absorbing layer. The observation from the previous work showed optimal thicknesses of 8 and 138 mm for the CFRP and steel layers, respectively.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The titanium layer and the aluminum layer were simulated as reflecting and absorbing members, respectively. Moreover, the optimal hybrid system containing CFRP and steel layers that was subjected to the same explosion source was also found with the present work [ 23 ]; the CFRP layer was considered as a reflecting layer, and the steel layer was considered as an absorbing layer. The observation from the previous work showed optimal thicknesses of 8 and 138 mm for the CFRP and steel layers, respectively.…”
Section: Resultssupporting
confidence: 71%
“…For practical modeling, it is worth considering the material behavior under the strain loading rate [15][16][17][18]. Because deterministic explosion simulation cannot provide a powerful design, given the considerable sensitivity of explosion simulation to many unclear parameters controlling the explosion [19], a reliability-based approach for designing explosion-proof composites has been suggested [20][21][22][23]. The literature review showed the tremendous application of CFRP on strengthening old structures as well as independent members for resisting explosive impact.…”
Section: Introductionmentioning
confidence: 99%
“…에 대한 기존의 연구에서 찾아 볼 수 있다 (Sheyka et 기존의 연구에서 에너지 al. 2011, Kim et al, 2012. 를 저항하고 흡수하는 구조로 각각 티타늄과 알루미 늄이 제안되었고 더 큰 충격하 (Sheyka et al 2011 (Biggs 1982, Chopra 2001 .…”
unclassified